STRATEGI PEMASARAN UMKM KEBAB DAN BURGER UNTUK MENINGKATKAN OMZET DAN DAYA SAING DI BARUGA STREET FOOD KOTA PALU SULAWESI TENGAH - Esra Citra Togatorop; Eva Afrilia; Alya Sasabila Yabiy; Suasa Suasa; Dandan Haryono; Nurhayati Hamid (JURNAL AKADEMIK PENGABDIAN MASYARAKAT, 2025)
This article examines the importance of marketing strategies for Micro, Small and Medium Enterprises (MSMEs) in the culinary field, particularly in the kebab and burger business, when facing increasingly fierce competition. Referring to Kotler's 4P marketing theory, this study explores the elements of product, price, place, and promotion that need to be optimized to increase the income and competitiveness of MSMEs. The method applied is qualitative, with data collection through interviews and documentation at Baruga Street Food, Palu City. The findings show that many MSMEs still rely on traditional marketing techniques, while the use of social media and digital marketing is still minimal. However, there are great opportunities to increase business growth through product innovation and the use of online platforms. Therefore, it is important to improve understanding of effective marketing strategies for the sustainability and development of MSMEs in the region.